Explanatory effects of young childhood caregiving environment, child's pro-social behavior, and child self-regulation skills on adolescent problem behavior. (May 2019) - Sohn, Byoungduk; Buchanan, Ann; Heo, Kay H.; Lee, Jane J.
Highlights: This study shows the links between children's behavior in the early years (age3/4) and links this with outcomes in early adolescent age 11/12 using the Millennium cohort Study from the UK while controlling for a range of family and other variables. Although there has been research that looks at parenting in the early years, to date we are not aware of any research that shows associations between a child's self-regulating behavior and outcomes in adolescence. The large data analysis that is possible in using the MCS, gives greater confidence in findings than findings from research at one time period.